Rapid dehydration of grape berries dampens the post-ripening transcriptomic program and the metabolite profile evolution. (1st September 2020) - Zenoni, Sara; Amato, Alessandra; D'Incà, Erica; Guzzo, Flavia; Tornielli, Giovanni Battista
Abstract: The postharvest dehydration of grape berries allows the concentration of sugars and other solutes and promotes the synthesis of metabolites and aroma compounds unique to high-quality raisin wines such as the passito wines made in Italy. These dynamic changes are dependent on environmental parameters such as temperature and relative humidity, as well as endogenous factors such as berry morphology and genotype, but the contribution of each variable is not well understood. Here, we compared berries subjected to natural or accelerated dehydration, the latter driven by forced air flow. We followed the evolution of transcript and metabolite profiles and found that accelerated dehydration clearly dampened the natural transcriptomic and metabolomic programs of postharvest berries. We found that slow dehydration over a prolonged duration is necessary to induce gene expression and metabolite accumulation associated with the final quality traits of dehydrated berries. The accumulation of key metabolites (particularly stilbenoids) during postharvest dehydration is inhibited by rapid dehydration conditions that shorten the berry life time.